Urgensi Bagi Pendidikan di Negera Indonesia yang sedang Berkembang - Eka Mei Riska Sitepu; Johana Andriani Nainggolan; Roselli Anjelina Lumbansiantar (JURNAL EDUKASI NONFORMAL, 2023)
Improving the quality of human resources is a mandatory requirement to achieve the goals to be achieved. Education is one way to improve the quality of human resources, so that education must always be improved. On the contrary, it is very important for success that the quality of human resources is improved through systematically implemented educational programs oriented towards scientific and technological interests. Moreover, seeing the times that are increasingly developing and the number of emerging technologies that are increasingly developing, of course, many problems will arise. For this reason, a critical way of thinking is needed on how to solve the problem. To solve this problem, a qualitative method was used by collecting data through literature study. The purpose of this paper is to examine what philosophy is and how important it is and its function in solving problems for education. In education, philosophy has an important role in formulating educational goals, developing theoretical foundations, building ethics and morality, and developing critical thinking skills. Through philosophy, education can become more meaningful, relevant, and prepare young people to face the challenges and complexities of a rapidly changing world